Phenotypic variability in patients with osteogenesis imperfecta caused by BMP1 mutations. Issue 12 (30th August 2016) - Pollitt, Rebecca C.; Saraff, Vrinda; Dalton, Ann; Webb, Emma A.; Shaw, Nick J.; Sobey, Glenda J.; Mughal, M. Zulf; Hobson, Emma; Ali, Farhan; Bishop, Nicholas J.; Arundel, Paul; Högler, Wolfgang; et al.
Abstract : Osteogenesis Imperfecta (OI) is an inherited bone fragility disorder most commonly associated with autosomal dominant mutations in the type I collagen genes. Autosomal recessive mutations in a number of genes have also been described, including the BMP1 gene that encodes the mammalian Tolloid (mTLD) and its shorter isoform bone morphogenic protein‐1 (BMP1). To date, less than 20 individuals with OI have been identified with BMP1 mutations, with skeletal phenotypes ranging from mild to severe and progressively deforming. In the majority of patients, bone fragility was associated with increased bone mineral density (BMD); however, the full range of phenotypes associated with BMP1 remains unclear. Here, we describe three children with mutations in BMP1 associated with a highly variable phenotype: a sibship homozygous for the c.2188delC mutation that affects only the shorter BMP1 isoform and a further patient who is compound heterozygous for a c.1293C>G nonsense mutation and a c.1148G>A missense mutation in the CUB1 domain. These individuals had recurrent fractures from early childhood, are hypermobile and have no evidence of dentinogenesis imperfecta. The homozygous siblings with OI had normal areal BMD by dual energy X‐ray absorptiometry whereas the third patient presented with a high bone mass phenotype. Intravenous bisphosphonate therapy was started in all patients, but discontinued in two patients and reduced in another due to concerns about increasing bone stiffness leading to chalk‐stick fractures. Given the association of BMP1 ‐related OI with very high bone material density, concerns remain whether anti‐resorptive therapy is indicated in this ultra‐rare form of OI.© 2016 Wiley Periodicals, Inc.